(untitled) - Smith, Janice Gorzynski (Boston, 2011)
Organic Chemistry accents basic themes in an effort to keep memorization at a minimum. Relevant examples from everyday life are used to illustrate concepts, and this mate- rial is integrated throughout the chapter rather than confi ned to a boxed reading. Each topic is broken down into small chunks of information that are more manageable and easily learned. Sample problems are used as a tool to illustrate stepwise problem solving. Exceptions to the rule and older, less useful reactions are omitted to focus attention on the basic themes.
Keywords: Chemistry, Organic,Hóa hữu cơ